Pengaruh Kualitas Pelayanan dan Periklanan terhadap Keputusan Nasabah dalam Menabung pada Bank Syariah (Studi Kasus pada BTN Syariah Surakarta) - Helmi Haris; Nur Said Irham T (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2012)
This research aims to analyze the influence of service quality and advertisingpartially and simultaneously against the costumer decisions in saving money at Bank Tabungan Negara (BTN) Syariah Surakarta. The population in this research are the total number of clients who save in Bank Tabungan Negara (BTN) Sharia Surakarta and using the Accidental Sampling as the method in sampling (numbers of sample are 98 respondent). The analysis tool that used in this research is “multiple linear regression”, which previously tested the validity and realibility as well as the classic assumption test. Based on the partial testing, both of service quality and advertising have significant influence positively with the level of á = 5% (0,05). The simultaneous test showed that the influence of service quality and advertising is significant with calculate F value 29.629 and the value of F table is 3.09